Stress reactions in the elbow region in tennis players - Rades, C. B. (1997)
Stress fractures are rare in comparison with acute traumatic fractures, accounting for between 3 and 5% or all overuse injuries in athletes. Two of these rare cases in tennis players are presented here. 1) A 24-year-old make top ten professional tennis player complained of chronic pain in the forearm. X-ray did not show any pathologic changes in bone structure, but a radionuclide bone scan confirmed the diagnosis of a stress reaction of the proximal ulnar diaphysis. After conservative treatment, including rest and therapy, the patient returned to his former level of professional tennis within a few weeks. 2) A 19-year-old female tennis player (recreational level) had been operated previously for `tennis elbow', without X-ray. Plain radiographs of the elbow suggested a stress fracture of the olecranon. This was confirmed by 3-dimensional CT. Treatment in this case was surgical, involving excision of the tip of the olecranon.